Salience of inherited wealth and the support for inheritance taxation - Spencer Bastani; Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2019)
We study how attitudes to inheritance taxation are influenced by information about the role of inherited wealth in society. Using a randomized experiment in a register-linked Swedish survey, we find that informing individuals about the large aggregate importance of inherited wealth and its link to inequality of opportunity significantly increases the support for inheritance taxation. The effect is almost uniform across socio-economic groups and survives a battery of robustness tests. Changes in the perceived economic importance of inherited wealth and altered views on whether luck matters most for economic success appear to be the main driving factors behind the treatment effect. Our findings suggest that the low salience of inherited wealth could be one explanation behind the relatively marginalized role of inheritance taxation in developed economies.
Keywords: D31; H20; H31; 330; Capital taxation; Tax attitudes; Equality of opportunity; Randomized experiment